At the End of Night: explorations of Antarctica and Space in the sound art of Philip Samartzis. Issue 2 (3rd July 2017) - Philpott, Carolyn; Samartzis, Philip
Abstract: This article explores the work of Australian sound artist Philip Samartzis, who documented the eco-acoustic characteristics and atmospheric effects of Antarctica and its environs during two field trips in 2010 and 2016. It begins by situating his work within the context of other compositions that engage with Antarctica, the atmosphere and Outer Space, before focusing on examples of two of his compositions. At the End of Night is based on sound recordings of a Medium Frequency Spaced Array radar used to measure upper atmospheric conditions through the transmission and reception of coded sine tone pulsations, while Aurora Australis is derived from the sonification of digital data generated by auroral activity produced over one calendar year. The article concludes with a section in which the composer reflects on Antarctica and its soundscape ecology, as well as the methods and processes he has employed whilst conducting field work in this extreme environment. In doing so, it aims to reveal the approaches and methods behind his sound art and to show how his compositions can not only enhance general understanding of Antarctica and the Earth's atmosphere, but also encourage us to engage with these spaces in new, and powerfully affecting, ways.